Epidemiological trends and risk factors related to lower urinary tract symptoms around childbirth: a one-year prospective study - Xiaojuan Wang; Hongyan Wang; Ping Xu; Minna Mao; Suwen Feng (BMC, 2023)
Abstract Background Lower urinary tract symptoms (LUTS) are prevalent and distressing concerns for women worldwide. The prevalence of LUTS reaches the first peak during pregnancy and postnatal period. However, less attention has been paid to LUTS around childbirth and little progress has been made in the prevention of LUTS. Understanding the epidemiological characteristics of LUTS around childbirth would inform decision making for health care providers and perinatal women in the prevention of LUTS. The study aims to investigate the epidemiological trends and associated risk factors related to LUTS around childbirth. Methods Pregnant women were consecutively enrolled during pregnancy in the obstetrical wards of a tertiary hospital and followed up at 6-8 weeks and one year postpartum through a prospective design. Urinary incontinence was assessed with the International Consultation on Incontinence Modular Questionnaire-Urinary Incontinence Short Form. Other symptoms were measured with questions based on definitions of the International Incontinence Society. Multiple logistic regression was used to examine the risk factors for LUTS including urinary incontinence, increased daytime frequency, nocturia and urgency. The report followed the STROBE statement. Results A total of 1243 pregnant women participated in this study. The prevalence of at least one type of storage symptoms was 94%, 55% and 35% in late pregnancy, at 6-8 weeks and one year postpartum, respectively. The prevalence of urinary incontinence remained at 21% within one year postpartum. The majority of the participants suffered from mild to moderate urinary incontinence. Age, job, BMI before pregnancy, gestational diabetes mellitus, urinary tract infection history, previous history of LUTS, age at first birth and birth mode were predictors of LUTS one year postpartum. Conclusion LUTS were highly prevalent during pregnancy and postnatal period. The prevalence of urinary incontinence was more stable than that of other LUTS within one year postpartum. Women aged more than 35 years, engaging in manual work, with gestational diabetes mellitus, with a history of urinary tract infection and LUTS, with advanced age at first birth and vaginal delivery were more likely to suffer from LUTS postpartum. The findings provided a novel and deep insight into the epidemiological trends and related risk factors of LUTS around childbirth.